'Minds Were Forced Wide Open': Black adolescents' identity exploration in a transformative social justice class. (July 2016) - Harrell-Levy, Marinda K; Kerpelman, Jennifer L; Henry, Daniel
Theories imply that transformative teaching influences positive identity development, but empirical studies of this relationship are sparse. It is clear that good teaching can positively influence youth; however, it is less clear how good teachers influence positive identity outcomes in youth, and in particular Black youth. We examined the identity exploration of 13 former Black students of a high school transformative social justice class. Drawing from a larger qualitative study that addressed transformative social justice and adolescent development, the current analysis focused on the subset of factors that contributed to identity exploration and beliefs about civic responsibility in one's career and personal life. Results revealed an emphasis on civic and career identity exploration, feeling agentic and self-assured, and reconsidering privilege. Findings are discussed in terms of transformative social justice enhancing Black youths' investment in their development.